(untitled) (Global Journal of Human-Social Science, 2020)
The issue of secularism in the African environment has been an age-long debate. This has attracted series of arguments and counter-arguments. Such controversies are expected given the religious and philosophical phenomenon and the African writers’ portrayal of religious role in African society. This paper’s goal is to assess the views of several African writers on the issue of secularism on the religious and philosophical themes of their writing. The major objective is to provide knowledge and tool to enable contributions of literature to African Traditional Religion, Christianity and Islam. The focus of the paper is on the African spiritual transformation which will constitute the main structure of the black race with it connection to general existence.